The y-intercept of g(x) is less than the y-intercept of f(x). (Option A).
How to calculate the equation of the line?
The equation of the given line is calculated by applying the following formula as shown below;
The general equation of a line is given as;
y = mx + c
where;
- m is the slope of the line
- c is the y - intercept of the line
The slope of the function f(x) is calculated as;
m = Δ y / Δ x
m = ( 0 - - 3) / ( 6 - 0)
m = 3 / 6
m = 1/2
The y - intercept of the line = - 3
The equation for the function f(x) is;
f(x) = x/2 - 3
We were given the function g(x) as;
g(x) = 6x - 36
So we can see that the y-intercept of g(x) is less than the y-intercept of f(x).
- 36 < - 3